RNA helicases, DDX5 and DDX17, facilitate lytic reactivation of gammaherpesviruses. - Praneet Kaur Sandhu; Blossom Damania (PLoS Pathogens)
Human gammaherpesviruses comprise of Kaposi's sarcoma-associated herpesvirus (KSHV) and Epstein-Barr virus (EBV), and are oncogenic viruses that cause life-long infections. The gammaherpesviruses utilize an extensive virus-host interaction network for facilitating viral replication, whereby virus-encoded proteins modulate host processes. Thus, identifying targets of viral proteins that aid in gammaherpesviral replication will help develop therapies to combat these viruses. We identified that host proteins DDX5 and DDX17 interact with gammaherpesviral protein kinases, KSHV-encoded vPK and EBV-encoded BGLF4. We found that DDX5 and DDX17 are required for gammaherpesviral lytic reactivation and loss of both DDX5 and DDX17 decreased KSHV and EBV lytic reactivation. Depletion of DDX5 and DDX17 lowered the transcription of KSHV RTA, the key viral gene that drives the lytic replication cascade, due to reduced occupancy of Brg1, a chromatin remodeler, at the RTA promoter. Consequently, inhibition of Brg1 decreased gammaherpesviral lytic reactivation. Here we demonstrate how gammaherpesviruses hijack the function of two host proteins to promote their lytic replication cycle.